"I can see you; I can feel it; and vice-versa": consciousness and its relation to emotional physiology. Issue 3 (2nd April 2020) - Tsikandilakis, Myron; Bali, Persefoni; Derrfuss, Jan; Chapman, Peter
ABSTRACT: In this paper, we explore whether masked emotional faces can elicit changes in physiology without awareness. We also explore whether emotional miss-discrimination involves the physiological correlates associated with the perception of an emotion. We adjust the discrimination threshold of presentation per participant and stimulus type to chance-level performance using hit rates and receiver-operating characteristics (ROC). We assess subliminality using an adjusted Bayesian criterion for awareness ( A  = .167). We measure skin-conductance, heart-rate, facial-emotional and engagement-task force-pressure responses to masked fearful, angry, happy, sad and neutral faces. We report that when faces were subjectively adjusted using unbiased ROC criteria for awareness, we found non-significant differences between emotions and Bayesian evidence for null responses. Hit-rate adjustments were associated with physiological changes for hits and misses for fearful, angry and happy faces. For misses for discrimination performance, participants could correctly appraise the valence and arousal of the presented face. Miss-discrimination for seeing a fearful face when presented with innocuous cues was also associated with high arousal responses. These findings suggest that if physiological arousal is elicited during the presentation of masked emotion, conscious assessment is, upon explicit post-trial inquiry, involved in the evaluation of the elicited emotion and the emotional elicitor.